Analisis Pengaruh Pengajaran Yesus Pengudus Terhadap Penyalahgunaan Alkohol (Antiseptik) Di Kalangan Pemuda Di Gereja Kemah Injil Indonesia Jemaat Teluk Selimau Kabupaten Bulungan - Lian, Desem; Panggarra, Robi; Tarigan, Simon; Lele, Aldorio F. (Jurnal Kala Nea, 2023)
The purpose of writing this thesis is to find out how far the influence of the teachings of Jesus the sanctifier on alcohol abuse among youth at the Indonesian Gospel Tent Church, the Teluk Selimau Congregation, Bulungan Regency. The method used in this writing is to use qualitative methods. And to conduct field research, the thing that was done for data collection was by interviewing several youths, including pastors and customary heads who were in Selimau Bay, then managing it qualitatively. As for the indicators that the researchers found as the cause of the decrease in attendance at worship, the interest in serving was due to: First, Less in-depth teaching. Second, the time of teaching. The conclusion from the discussion of this thesis is First, the teaching carried out by the pastor focuses on each of the themes that have been determined so that the teaching of the fourfold gospel does not focus on teaching. Second, young men and women think that the four-fold gospel is only a logo, not a teaching.